2022
DOI: 10.3389/fsurg.2022.843982
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of the Treatment of Primary Trigeminal Neuralgia by Percutaneous Balloon Compression

Abstract: PurposeTo summarize the technical points and clinical effects of percutaneous balloon compression (PBC) in the treatment of primary trigeminal neuralgia.MethodsThe clinical data of 13 patients with trigeminal neuralgia who received PBC from April 2020 to July 2021 were retrospectively analyzed. VAS, VRS-4 and PPI were used to evaluate the postoperative pain relief. Different postoperative complications were analyzed.ResultsAll patients had a smooth operation, the inflation volume of the balloon was 0.7 ml, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Because of its minimal invasiveness, quick recovery after surgery, and immediate pain relief, PBC is gradually becoming an attractive choice for the treatment of TN, especially in those patients who refuse to undergo open surgery [ 20 , 21 ]. PBC is an effective and safe option for the elderly population and patients with recurrence after MVD or other unsuccessful treatment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of its minimal invasiveness, quick recovery after surgery, and immediate pain relief, PBC is gradually becoming an attractive choice for the treatment of TN, especially in those patients who refuse to undergo open surgery [ 20 , 21 ]. PBC is an effective and safe option for the elderly population and patients with recurrence after MVD or other unsuccessful treatment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have analyzed the relationship between balloon compression time and postoperative facial numbness. Wang H et al [13] reported an average balloon compression time of 120 s, ranging from 30 to 180 s, with postoperative ipsilateral facial numbness in 12 cases (92.3%) and severe numbness in one patient. Valenzuela Cecchi B et al [2] conducted a 10-year follow-up of 29 TN patients treated with PBC, with 18 of them showing mild symptoms of facial numbness.…”
Section: Discussionmentioning
confidence: 99%
“…PBC was recommended as the first-choice percutaneous procedure for the treatment of TN, and the efficacy and safety had been demonstrated. 6 , 7 , 21 However, PBC-induced TCR has been reported in numerous studies, 22 which is characterized by significant hemodynamic changes that may be fatal to elderly patients. The TCR is known to occur suddenly without any signal at the moment of puncturing the foramen ovale and compressing the trigeminal ganglion during PBC.…”
Section: Discussionmentioning
confidence: 99%